Theoretical probability of paternity ascertainment and enlarged set of serological tests - Przybylski, Zygmunt (Anthropological Review, 1976)
The question of theorelical possibilities for paternity ascertainment is frequently raised by lawyers and physicians, because result of serological expertise is one of the main evidences in legal procedure aimed at establishing a material truth in cases of uncertain parenthood. Since, until now in Poland the expertises of this sort were based only on examination of systems: ABO, AA, MN, Rh (Cw, Cc, D, Ee), Kell, Hp, Gm(a) it is important to determine to what extent inclusion of further systems (AcP, Fyab, Jkab, Ss, Ge, PGM, Gm2, InV1, Lea, Xga, ADA, AK, Lua, Gm5 and eventually HL-A) into the expertise coulol raise the probability of exclusion from a paternity case a man who is not a biological father. In this purpose there were made numerous examinations of unrelated persons (485 - 5824 individuals from Great Poland region). Respective gene frequencies were calculated together with a probability of non-father exclusion in a paternity expertise. The most important conclusions of this paper are as follows: 1. Theoretical probability of non-father exlusion is in population of Poznań around 67% while examining AB0, Mn, Rh, Kell, Hp, Gm(1) and Sese systems. 2. This probability could be increased to around 94% after inclusion of new systems mentioned above into expertise. 3. Among those systems group of erythrocyte enzymes deserves special attention. 4. AcP system gives alone about 25%o probability of non-parent exclusion, hence introduction of this system into routine expertises is fully justified. 5. Among the rest of erythrocyte enzyme systems it is advisable to utilize in paternity expertises phosphoglukomutase system, which gives an exclusion chance about 15%. 6. Serum protein Gc system should be widely introduced into practice, it gives the exclusion probability 16%, hence it is almost equal in this respect with Hp system. 7. Further serum protein systems: Gm(1), Gm(2) and InV(1) give similar probabilities (around 8%) 8. Systems Fyab and Jkab giving high exclusion probabilities (above 18%) should be soon introduced into paternity expertises. 9. Exclusion probability with use of HL-A system only is 67,53%. Joining this with the chance given by 22 other systems raises overall exclusion probability from 93,79% to almost 98%.